2009
DOI: 10.1074/jbc.m109.032086
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Gene Silencing by the SRY Protein Is Mediated by a KRAB-O Protein That Recruits the KAP1 Co-repressor Machinery

Abstract: The sex determination transcription factor SRY is a cell fatedetermining transcription factor that mediates testis differentiation during embryogenesis. It may function by repressing the ovarian determinant gene, RSPO1, action in the ovarian developmental pathway and activates genes, such as SOX9, important for testis differentiation at the onset of gonadogenesis. Further, altered expression of SRY and related SOX genes contribute to oncogenesis in many human cancers. Little is known of the mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 36 publications
(36 reference statements)
4
69
0
Order By: Relevance
“…A number of proteins, including KRABO (kruppel-associated box domain only) (Oh et al, 2005;Peng et al, 2009), WT1 (Wilms tumour 1) (Matsuzawa-Watanabe et al, 2003), SIP1 (SRYinteracting protein 1) (Poulat et al, 1997) and PARP1 [Poly (ADPribose) polymerase] (Li et al, 2006) have been shown to interact with mouse and human SRY (Fig. 3A).…”
Section: Sry Structure and Functionmentioning
confidence: 99%
“…A number of proteins, including KRABO (kruppel-associated box domain only) (Oh et al, 2005;Peng et al, 2009), WT1 (Wilms tumour 1) (Matsuzawa-Watanabe et al, 2003), SIP1 (SRYinteracting protein 1) (Poulat et al, 1997) and PARP1 [Poly (ADPribose) polymerase] (Li et al, 2006) have been shown to interact with mouse and human SRY (Fig. 3A).…”
Section: Sry Structure and Functionmentioning
confidence: 99%
“…On the other hand, two recent genome-wide localization studies revealed that the association with nuclear lamina was mostly characterized by a repressive chromatin environment, devoid of active histone marks and RNA polymerase II binding activities (Pickersgill et al, 2006;Guelen et al, 2008). Of interest, one demonstrated SRY partner protein is KRAB-O, which by means of KAP-1 is able to recruit histone deacetylase and HP1 heterochromatin protein (Peng et al, 2009). Thus, the specific localization of gSRY protein in a repressed chromatin compartment could argue in favor of a repressive role for this sex-determining protein in the goat.…”
Section: Subcellular Localization Of the Proteinmentioning
confidence: 99%
“…Whereas in mice Sry can now be GOAT SRY PROTEIN EXPRESSION 3331 restricted to being a direct activator of Sox9, evidence has accumulated to suggest repressive actions for SRY in other species (McElreavey et al, 1993;Peng et al, 2009). According to (i) these repressive actions of SRY, (ii) the results of the present study, and (iii) our knowledge of Y chromosome evolution, we propose that the gonad role of Sry in the mouse has been narrowed during evolution to Sox9 activation in pre-Sertoli cells.…”
Section: What Might Explain Differences In Sry/sry Expression Betweenmentioning
confidence: 99%
“…2;Satou 2001;Li et al 2003;Satou et al 2004;Wang et al 2005Wang et al , 2007Jin et al 2007;Tsuruma et al 2007;Kamitani et al 2008Kamitani et al , 2011Peng et al 2009;Seki et al 2010;Liang et al 2011;Maruyama et al 2011;Huang et al 2013). For most of these, the KRAB-ZFPs included, TRIM28 functions as a co-repressor down-regulating gene transcription by its heterochromatin-inducing activity at its target sites (Iyengar and Farnham 2011;Cheng 2014).…”
Section: Trim28-a Multifaceted Worker In the Chromatin Fieldmentioning
confidence: 99%
“…Additional insights to TRIM28 function in vivo were gained from studies in preimplantation embryos (Satou 2001;Li et al 2003;Satou et al 2004;Wang et al 2005Wang et al , 2007Jin et al 2007;Tsuruma et al 2007;Kamitani et al 2008Kamitani et al , 2011Peng et al 2009;Seki et al 2010;Liang et al 2011;Maruyama et al 2011;Huang et al 2013). TRIM28 attracts chromatin writers and readers (right) (Nielsen et al 1999;Ryan et al 1999;Schultz et al 2001Schultz et al , 2002Quenneville et al 2011;Zuo et al 2012).…”
Section: Trim28-a Multifaceted Worker In the Chromatin Fieldmentioning
confidence: 99%